Systematic revision of Afrogecko ansorgii (Boulenger, 1907) (Sauria: Gekkonidae) from western Angola - Lobon-Rovira, Javier; Conradie, Werner; Pinto, Pedro Vaz; Keates, Chad; Edwards, Shelley; Plessis, Anton Du; Branch, William R. (Zootaxa, 2022)
Here we provide the first phylogenetic analysis that include Afrogecko ansorgii and a detailed morphological comparison with other species of leaf-toed geckos. For this purpose, we used two mitochondrial (16S, ND2) and four nuclear (RAG1, RAG2, CMOS, PDC) genes to produce a robust phylogenetic reconstruction. This allowed us to show that A. ansorgii is not related as previously believed to circum-Indian Ocean leaf-toed geckos and is rather more closely related to other Malagasy leaf-toed geckos. Additionally, we explore and compare osteological variation in A. ansorgii skulls through High Resolution X-ray Computed Tomography with previously published material. This allowed us to describe herein a new genus, Bauerius gen. nov., and additionally provide a detailed redescription of the species (including the first description of male material), supplementing the limited original description and type series, which consisted of only two females.